2016
DOI: 10.1016/j.ijgfs.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Imagined salad and steak restaurants: Consumers’ colour, music and emotion associations with different dishes

Abstract: The aim of the present study was to examine people's colour, music and emotion associations with dishes from two imagined restaurants. We conducted an experiment where we asked two study-participant groups to match interior colours, background music and desired emotional states for either a salad restaurant or a steak restaurant. To evoke associations we used two dish photos -a salad and a steak dish. The hypothesis was that the study participants would choose different background music and colours for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
(46 reference statements)
0
7
0
2
Order By: Relevance
“…Nevertheless, to summarize, those companies packaging their leafy (salad) greens would be well advised to check which background colour makes the transparent packaging of their greens look their best, as the evidence that has been published to date clearly suggests that it makes a difference. There is even evidence to suggest that certain background colour schemes might be more appropriate for a salad (vs. say a steak) restaurant (Kontukoski, Paakki, Thureson, Uimonen, & Hopia, 2016). Perhaps unsurprisingly, the participants quizzed in this particular study suggested a green colour scheme for a salad restaurant while instead going for red for a steak restaurant instead.…”
Section: Insert Figure 3 About Herementioning
confidence: 74%
“…Nevertheless, to summarize, those companies packaging their leafy (salad) greens would be well advised to check which background colour makes the transparent packaging of their greens look their best, as the evidence that has been published to date clearly suggests that it makes a difference. There is even evidence to suggest that certain background colour schemes might be more appropriate for a salad (vs. say a steak) restaurant (Kontukoski, Paakki, Thureson, Uimonen, & Hopia, 2016). Perhaps unsurprisingly, the participants quizzed in this particular study suggested a green colour scheme for a salad restaurant while instead going for red for a steak restaurant instead.…”
Section: Insert Figure 3 About Herementioning
confidence: 74%
“…Besides the tangible aspects of service system design, atmospherics may play an important role with regards to situationally conditioned food scenarios (Kontukoski, Paakki, Thureson, Uimonen, & Hopia, ) and eating (Wansink, ; Weber, King, & Meiselman, ). Exemplarily, a study by García‐Segovia et al () indicated a relationship between the perception of food and the table (i.e., plastic plate on plain table compared to porcelain plate on table with tablecloth) and service setting (i.e., classroom compared to restaurant) in which it is served.…”
Section: Resultsmentioning
confidence: 99%
“…Both scent and background music have an impact on customer behavior and satisfaction [ 96 ]. Consumers associate different bars and dishes with certain scents and musical accompaniments [ 97 ]. P24: In addition to taste, scent will play a more important role in the next five to ten years.…”
Section: Methodsmentioning
confidence: 99%